THE NEXUS BETWEEN COMMUNITY PARTICIPATION IN CONSERVATION AND LAND COVER CHANGE IN KAKAMEGA FOREST, KENYA - Laura, Agweyu; Dr. Raphael Mulaha Kweyu,; Dr. Kibutu Thomas, (IJRDO - Journal of Social Science and Humanities Research, 2020)
Participatory Forest Management (PFM) is essential for sustainable forest management as it’s based on the assumption that the forest provide both tangible and intangible goods to forest adjacent dwellers. In Kenya PFM is provided under the Forest Conservation and Management Act (2016). The law is meant to ensure that degradation of forests was halted but at the same time forest adjacent communities benefit from forest goods and services. A lot of studies have been carried out on the extend of forest cover change in major forest towers but there is limited information on the relationship between community participation in forest conservation and its effect on forest cover change on Kakamega Forest. The level of water has reduced gradually in some of the rivers whose source is Kakamega forest due to forest cover loss. The study targeted FAC that included CFA members at 5km radius from the forest edge in Shinyalu, Kenya Forest Service (KFS) officers, and Community Based Organization (CBO) leaders. The target population on land cover change information was composed of images acquired from 1998 to 2018. A sample size of 187 CFA members was selected using simple random and purposive sampling method was used to select 7 CBO leaders and one KFS officer. Data was collected using questionnaires, focused group discussions, interview schedules and remotely sensed satellite images. Data from questionnaires was analyzed using Statistical Package for Social Sciences (SPSS) software i.e.-frequencies, percentages, means and standard deviations and presented in form of tables. Medium resolution satellite data was analysed both spatially and statistically. Spatially, the extent of the area covered by different land cover types in Kakamega Forest in 2000, 2008 and 2018 was captured on different satellite image data sets using Geographical Information System (GIS) software. The study findings revealed that various Kakamega forest land classes increased between 2000-2008 due to CFA activities like afforestation, reforestation and agroforestry but the forest cover declined within the period of 2008-2018 except grassland vegetation which increased all through. Study findings indicate that some of the activities that increased the forest cover included afforestation, reforestation and agroforestry Training of more CFA scouts and deployment of additional rangers to man the vast forest alongside creating awareness through chief baraza to the local community on the need for conserving kakamega forest was recommended.